ВИКОРИСТАННЯ ТЕХНОЛОГІЇ “ДІАЛОГУ КУЛЬТУР” У ПРОЦЕСІ ДИДАКТИКО-МЕТОДИЧНОЇ ПІДГОТОВКИ ВЧИТЕЛІВ ПОЧАТКОВИХ КЛАСІВ (Педагогіка вищої та середньої школи, 2022)
The problem of upgrading professional preparation of the future teachers of the primary schools by using of the innovative technology dialog of cultures is examined in the article. This didactic technology formers for students and pupils harmonic vision of the world influences on the personality cognition of surrounding reality.